Syn-sedimentary deformation structures in the Early Miocene lacustrine deposits, the basal limestone unit, Bigadiç basin (Balikesir, Turkey) - Koç-Taşgin, Calibe; Türkmen, Ibrahim; Diniz-Akarca, Cansu (General Directorate of Mineral Research and Exploration (MTA), 2018)
In the Western Anatolian region, NE-SW, E-W directional basins were developed which were limited to the extension-related faults beginning in the late Oligocene to early Miocene. The fillings of these basins consist of fluvial - lacustrine deposits containing volcanic and volcaniclastic intercalations. These deposits include intensive local unconformities and soft sediment deformation structures. The filling of the Bigadiç Neogene Basin which is one of these basins, constitute base limestone unit, lower tuff unit, lower borate unit, upper tuff unit and upper borate unit. The base limestone unit composed of claystone, marl, limestone, dolomitic limestone facies was deposited in the deep lacustrine environment. The soft sediment deformation structures were defined in the base limestone unit, which outcroped in the south of Bigadiç. These are: slumps, rock falls, chaotic structures, clastic dykes, synsedimentary faults and breccia limestone. Deformation mechanisms are related essentially to the increase of slopes of layers, liquidization and fluidization. In the study area; regional tectonics, sedimentological data, and deformation structures are evaluated together, it is concluded that these structures are formed by tectonic and seismic (earthquakes related to tectonic origin and syndepositional magmatic activities). © 2018 General Directorate of Mineral Research and Exploration (MTA). All rights reserved.
Bigadiç havzasi (Balikesir-Türkiye) Erken Miyosen göl çökellerinde sin-sedimanter deformasyon yapilari, taban kireçtaşi birimi
Keywords: Bigadiç; Lacustrine; Rock falls; Slumps; Soft sediment deformation structures